Strategi Advokasi Kesehatan Dalam Pencegahan Anemia Pada Remaja Putri Di Sumatera Utara : Literature Review - Anisah Fitri Rahmasari Harahap; Cynthia Winanda; Afzidan Lutfi Amaryu Marpaung; Selamat Ariady Tampubolon; Miftahurrahmah El Hayatli (Annusfy : Journal of Multidisciplinary Research, 2026)
Anemia among adolescent girls remains a public health problem in North Sumatra, requiring effective health advocacy strategies to support prevention efforts. This study aimed to analyze health advocacy strategies for anemia prevention among adolescent girls in North Sumatra.  A descriptive qualitative literature review was conducted using 10 scientific articles published between 2021 and 2026, identified through Google Scholar and national scientific journals. The findings showed that the main health advocacy strategies included health education, strengthening the Iron Supplementation Tablet (IST) program, promoting nutritious local foods, and multi-sectoral collaboration. These strategies improved knowledge, awareness, and preventive behaviors among adolescent girls. In conclusion, health advocacy is an essential strategy for anemia prevention and requires collaboration among stakeholders to ensure effective and sustainable prevention programs.